Analisis Strategis Public Relations Ruang Guru Dalam Upaya Membangun Branding Sebagai Platform Mitra Belajar Daring - Syuryatman Desri; Mutiara Citra Sari; Sarah Faikhotul Fadilla; Widia Khairani; Salima Shindi Sabila (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Ruangguru is a bold educational application based in Indonesia. Ruangguru provides a variety of educational services, including tutoring, online classes, learning materials, and various educational resources. descriptive research method with a case study approach. Ruangguru's public relations primarily relies on news media, especially digital news. In the evaluation stage, at the evaluation preparation level, Ruangguru Public Relations has made preparations before implementing the program. Ruangguru Public Relations has key performance indicators in the form of total coverage and total engagement, total articles distributed, and number of interviews with the media.